A comparative study of wavelet families for classification of wrist motions - Muthusamy, Hariharan; Chong, Yen Fook; Sindhu, Ravindran; Bukhari, Ilias; Sazali, Yaacob, Prof. Dr. (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/